Comprehensive assessment of menstrual cup awareness and utilization among degree students - Gottiparti, Varalaxmi; Jose, Amisha; E. V., Ayana; Sravani, Sheelam; Deepika, Madanu; Jose, Aleena; Anusha, Thakur; Babu, Roslin; Swetha, Uyyala; Maheswari, Vallapudasu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menstrual hygiene management poses significant challenges for girls in low-income environments, particularly in educational settings, where cultural norms, inadequate knowledge of recommended hygiene practices, and restricted access to affordable menstrual products hinder effective menstrual care. The vaginal menstruation cup emerges as a potential alternative to traditional sanitary pads or tampons, offering a sustainable and cost-effective solution. Methods: The research approach was quantitative research, and the research design adopted was a one-group pre-test and post-test design. The study was conducted among college students at selected colleges in Suryapet. The sample size was 60. The non-probability purposive sampling technique was used. Results: Assessment of knowledge was done using a self-administered questionnaire, and practice was done using an observational checklist. Analysis showed that the pre-test mean knowledge score was 5.61±1.16 and the post-test mean knowledge score was 17.86±1.46. The pre-test mean practice score was 2.79±1.18, and the post-test mean practice score was 10.37±1.36. Analysis also reveals that (r =0.340, p = 0.009) a positive correlation was found between the knowledge and practice scores of students regarding menstrual cups. Analysis also reveals the calculated ‘t’ value for knowledge, i.e., 49.52, which shows the demonstration of knowledge regarding menstrual cups among college students was effective. The calculated ‘t’ value for practice, i.e., 30.84, shows the demonstration in practice was effective. Conclusions: The study concludes that knowledge scores were associated with age, type of family, and education. Therefore, by statistically interpreting the data, the demonstration of knowledge and practice regarding menstrual cups among college students was effective. Consequently, the alternative hypothesis is accepted.